L'immagine del cane in Franz Kafka - Pastorelli, Giuseppina (Premio Tesi di Dottorato, 2015)
Within the Kafkaesque bestiary, the dog is undoubtedly the animal that deserves a more careful study: it is the image which the author uses the most, in literary writing but also in the private one, and which occupies a a very large time span, so much so that it becomes a real key figure through which to read Kafka's work from a possible new perspective. The volume aims to demonstrate how the problems that have characterized Kafka's existence are hidden behind the dog's symbology, the reflections around which he has concentrated, throughout his life, his thought and his writing: the woman and the question of marriage, writing itself, religion as a relationship with the divine.